A novel effect of bevacizumab in reducing characteristic pigmentation in Peutz–Jeghers syndrome: a case report and literature review - Wu, Delu; Liu, Xinyue; Wang, Song; Zhang, Huanyu; Qu, Guofeng; Wang, Lina (Frontiers in Oncology, 2026)
Peutz–Jeghers syndrome (PJS) is a rare autosomal dominant disorder characterized by mucocutaneous pigmentation (e.g., perioral melanotic macules) and gastrointestinal hamartomatous polyps, with heightened cancer susceptibility. This report describes a 34-year-old Han Chinese ethnicity woman with familial Peutz–Jeghers syndrome (PJS) and stage IIA HPV-independent gastric-type endocervical adenocarcinoma following bevacizumab therapy. Initial concurrent chemoradiation (paclitaxel with either nedaplatin or cisplatin with volumetric modulated arc therapy) achieved partial response, while subsequent maintenance therapy combining bevacizumab with chemotherapy induced complete radiographic remission. Crucially, progressive fading of pathognomonic perioral melanotic macules demonstrated temporal correlation with bevacizumab administration, with sustained remission at 1-year follow-up. These findings challenge the conventional paradigm of PJS pigmentation as a static feature by demonstrating that VEGF-mediated angiogenesis concurrently drives carcinogenesis and melanin deposition. The case highlights three key implications, namely: (1) validation of bevacizumab’s dual therapeutic potential against PJS-associated malignancies and cutaneous manifestations, (2) proposal of mucocutaneous pigmentation as a dynamic biomarker for treatment response monitoring, and (3) urgent need for prospective clinical trials evaluating VEGF inhibition in PJS through longitudinal surveillance of oncologic control and pigment dynamics.